Modernization of Islamic Education in South Kalimantan (Socio-historical Perspective of Normal Islam Amuntai) - M. Ali Sibram Malisi (Postgraduate Program, State Institute on Islamic Studies Purwokerto, 2017)
Islamic educational institutions not only survived, but also began in earnest to make certain adjustment by adopting certain aspects of European education. This can be seen in the rise of madrasah that introduced classical system and curriculum for instance. This in turn affected ‘traditional’ Islamic educational institutions such as pondok or pesantren to also modernize themselvesNormal Islam Amuntai as further developments of Arabische School (1938). This school use modern system but in understand strong hold on the mazhab. Normal Islam became the source of the birth of the madrasahs in Amuntai incorporated in Ittihad Ma'ahid al-Islamiyah (IMI). In addition to achievements in the field of the development of Islamic educational institution, the institution was also the locus of occurrence of social mobility in South Kalimantan Amuntai, among others, marked by the participation of alumni in the Affairs of its administrator and civic and political situation both local and national.